Nitrogen-doped carbon nanofibers derived from polyacrylonitrile for use as anode material in sodium-ion batteries. (November 2015) - Zhu, Jiadeng; Chen, Chen; Lu, Yao; Ge, Yeqian; Jiang, Han; Fu, Kun; Zhang, Xiangwu
Abstract: Nitrogen-doped carbon nanofibers (N-CNFs) derived from polyacrylonitrile were successfully synthesized by a combination of electrospinning and thermal treatment processes. The as-prepared N-CNFs were used as anode material for sodium-ion batteries due to their unique fabric and weakly-ordered turbostratic structure as well as large spacing between graphene layers. Results show that N-CNFs carbonized at 800 °C delivered a high reversible capacity of 293 mAh g −1 at a current density of 50 mA g −1 in the first cycle. Even though the first-cycle Coulombic efficiency was 64%, it increased to nearly 100% only after a few initial cycles. Additionally, these N-CNFs showed excellent cycling and high-rate performance, and maintained a capacity of up to 150 mAh g −1 even at an extremely high current density of 1000 mA g −1 for over 200 cycles. It is, therefore, demonstrated that N-CNFs prepared under appropriate conditions are promising anode material candidate for sodium-ion batteries.